CONHECIMENTO E GESTÃO DO CONHECIMENTO CIENTÍFICO: UM ESTUDO REALIZADO JUNTO A DOCENTES DE UM CURSO DE MESTRADO EM ADMINISTRAÇÃO - Graziela Oste Graziano Cremonezi (Revista Gestão Universitária na América Latina, 2013)
A new model of flexible administration and based on the knowledge it requests the worker manager, fact that has been demanding the search from the companies for a new profile of interested collaborators in processes of continuous and progressive learn ing. The present article presents part of a study accomplished with teachers doctors, allocated in a master's degree program in Administration. In that context, the proposal of the study is anchored in the line of understanding search on the forms and lear ning processes, the nature of the cycle of conversion of the knowledge and the process of creation of the knowledge used by the teachers. For the collection of data a questionnaire was used with open and closed subjects. The results pointed the most usual practices adopted by the teachers in your learning processes and knowledge, as well as, your behaviors before the phases of the cycle of conversion of the knowledge.